The Effect of species on nutritive value and anti-methanogenic potential of vetch hays grown in native pasture in Turkey - Kaya, Emrah (Progress in Nutrition, 2021)
The aim of the current experiment was to determine effect of species on chemical composition, in vitro gas production, methane production, metabolizable energy (ME), organic matter digestibility (OMD), true substrate digestibility (TSD), partitioning factor (PF), microbial protein yield (MPY) and efficiency of microbial protein yield (EMP) of vetches grown in native pasture in Turkey.  The species had a significant effect on the chemical composition, in vitro gas production, methane production, ME, OMD, TSD, PF, MPY and EMPY of vetch hays.  Crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), gas production, methane production, ME, OMD, PF, MPY, EMPY and TSD ranged from 17.2 to 26.6 %,  41.3 to 61.5%, 23.3 to 39.2 %,  89.5 to 125.0 ml, 14.6 to 19.4 ml, 7.8 to 10.0 MJ (kg /DM), 60.2 to 74.1 %, 3.2 to 4.0, 107.1 to 173.5 mg, 31.9 to 44.2 % and 60.4 to 82.1 % respectively. There is considerable amount of variation among vetch hay samples in terms of chemical compositions, gas production, CH4 production, MPY, EMPY and the other estimated parameters such as ME and OMD. The vetch hays studied in the current experiment have a potential to meet the CP, ME and fiber requirement of ruminant animals for growth and lactation.  Based on the chemical composition and fermentation parameters, Vicia villosa can be recommended for hay production since it has a high CP, MPY and EMPY. However, before large implication the biomass yield of vetch species should be tested.